Wear and compression behavior study of carbon nanotube in aluminium Nano composites - S. Hatti, Prashant; K. Narasimha, Dr; B. Somanakatti, Anupama (International Journal of Engineering and Technology, 2018)
In this study, carbon nanotube (CNT) reinforced in aluminium (Al) matrix for different weight percentages were fabricated by powder metallurgy (PM). A mechanical mixing process i.e. ball milling which employs mechanical alloying technique and results in effective dispersion of CNTs in aluminium powder was employed and two different ball materials namely tungsten ball and aluminium oxide ball was used for same composition of CNT/Al composites in order to understand different mill ball material effects on mechanical properties of CNT/Al composites. The powder mixtures were consolidated by microwave sintering. The microstructural analysis of both ball milled powder and sintered specimen were carried out where in case of powder samples effective dispersion of CNTs in aluminium powder was observed and in case of solid sintered samples the grain boundaries and bonding between the particles was observed. The wear test, the compression test of CNT and Al composites was carried out. The considered weight percentages varied from 0.5% to 1.3% for both alumina ball milled and tungsten ball milled specimens. The alumina ball milled specimens was observed to have high compressive strength and improved wear behaviour compared to tungsten ball milled specimens but in both cases 1.3 wt. % CNT reinforced samples showed best results. With CNT reinforcement Al, grains were refined under the pinning effect of CNTs at grain boundaries. The results proved that the alumina ball milled samples with 1.3 wt. percentage CNT reinforced composites had improved compression and wear behavior.Â Â